Development of a blended teaching module on integrated moral-art education to promote college students' moral level and psychological health - Jinzhang Leng; Nurfaradilla Mohamad Nasri; Khairul Azhar Jamaludin (Environment and Social Psychology, 2025)
Background: In the face of the increasingly prominent moral decline and psychological health problems of young college students around the world, such as the frequent occurrence of violence, crime and suicide, it has become a common topic of global education reform and development. Emphasizing and strengthening the moral education and psychological health of young college students has become a common topic of global education reform and development. Similar social cases are still on the rise, reflecting a deviation from the correct moral outlook. These cases also show that the traditional theory indoctrination teaching method of moral education can no longer achieve the goal of moral education for college students. Moral education and psychological health education need more attractive and emotional teaching materials and methods. Art education can make up for the "requirements" of students. This is because art education includes a variety of vivid, visual, and infectious materials and methods, such as painting, music, and calligraphy. The aim of this study is to develop a blended teaching module integrating moral education-art education to promote the moral and psychological health of university students. International organizations and governments around the world have reflected deeply on the crisis of moral education for young people facing the world today, which has finally evolved into a call for moral education. Subjects and Methods: The study selected a class of 40 students as a sample. The study was conducted in the form of a 40-person pre- and post-test. The test is based on effectiveness questionnaire. The questionnaires were completed before the start and after the end of the moral education and psychological health courses respectively. The questionnaire evaluated the effectiveness of teaching in the moral education and psychological health courses after using the new modules for teaching. Results: This study used SPSS v 28.0 to analyse and collect data. It was found that the students who were taught using blended teaching module on integrated moral-art education had significantly higher scores than those who were not taught using the blended teaching module. Their moral and psychological health scores were statistically higher than those before the course started. Conclusions: Using blended teaching module on integrated moral-art education for the course not only enhanced students' satisfaction, but also gained students' favor. At the same time, it has positive significance in promoting students' moral and psychological health levels.